Final‐year projects using open source OpenEEG. Issue 1 (8th September 2015) - Collins, Tim; Woolley, Sandra I.; Rawson, Nicholas C.; Haroon, Luth
ABSTRACT: Electronic Engineering undergraduates are increasingly interested in final‐year individual projects that involve brain–computer interfacing. This paper outlines the challenges of resourcing these types of medical instrumentation projects and describes the adoption of the open source OpenEEG electroencephalography platform in final‐year undergraduate projects. The OpenEEG projects applied a broad range of curriculum components including computer interfacing, signal processing, and software development. The applications were wide‐ranging and provided good opportunities to explore relevant research. The paper describes the initial investment in support required to resource the projects, in particular, the provision of supporting code examples. The projects were particularly popular with students. In total, twelve final‐year project students used the OpenEEG platform. Student engagement was good and the project outcomes were slightly above cohort average. © 2015 Wiley Periodicals, Inc. Comput. Appl. Eng. Educ. 24:156–164, 2016; View this article online atwileyonlinelibrary.com/journal/cae ; DOI10.1002/cae.21682